Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsami.9b11079
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Gas Sensors with Au Nanocluster Catalytic Overlayer: Toward Tuning Gas Selectivity and Response Using a Novel Bilayer Sensor Design

Abstract: Noble metals or oxide catalysts have traditionally been loaded or doped to enhance the gas sensing properties of oxide semiconductor chemiresistors. However, the selective detection of various chemicals for a wide range of new applications remains a challenging problem. In this paper, we propose a novel bilayer design with an oxide chemiresistor sensing layer and nanoscale catalytic Au overlayer to provide high controllability for gas sensing characteristics. The Au nanocluster overlayer significantly enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 54 publications
1
55
0
Order By: Relevance
“…Figure 14 shows four different examples that demonstrate the selectivity control of bilayer design sensors with nanoscale catalytic overlayers. [444][445][446] The thick films (thickness: ≈30 µm) with SnO 2 hollow spheres showed relatively low responses (R a /R g = 3.7-13.7) to 5 ppm ethanol, xylene, toluene, and benzene at 350 °C (Figure 14a1). [444] The decoration of SnO 2 film with Au nanoclusters by an e-beam coating of 0.5 nm thick (nominal thickness) Au and subsequent thermal annealing substantially enhanced the gas responses toward xylene and toluene (Figure 14a2).…”
Section: Bilayer Sensors With a Nanoscale Catalytic Overlayermentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 14 shows four different examples that demonstrate the selectivity control of bilayer design sensors with nanoscale catalytic overlayers. [444][445][446] The thick films (thickness: ≈30 µm) with SnO 2 hollow spheres showed relatively low responses (R a /R g = 3.7-13.7) to 5 ppm ethanol, xylene, toluene, and benzene at 350 °C (Figure 14a1). [444] The decoration of SnO 2 film with Au nanoclusters by an e-beam coating of 0.5 nm thick (nominal thickness) Au and subsequent thermal annealing substantially enhanced the gas responses toward xylene and toluene (Figure 14a2).…”
Section: Bilayer Sensors With a Nanoscale Catalytic Overlayermentioning
confidence: 99%
“…[444][445][446] The thick films (thickness: ≈30 µm) with SnO 2 hollow spheres showed relatively low responses (R a /R g = 3.7-13.7) to 5 ppm ethanol, xylene, toluene, and benzene at 350 °C (Figure 14a1). [444] The decoration of SnO 2 film with Au nanoclusters by an e-beam coating of 0.5 nm thick (nominal thickness) Au and subsequent thermal annealing substantially enhanced the gas responses toward xylene and toluene (Figure 14a2). The responses toward xylene and toluene became the highest (R a /R g = 61.4 and 56.2) when the thickness of the predeposited Au layer increased to 1.0 nm (Figure 14a3).…”
Section: Bilayer Sensors With a Nanoscale Catalytic Overlayermentioning
confidence: 99%
See 2 more Smart Citations
“…The research on gold nanoclusters (Au n ) started to attract extensive attention when Haruta et al [1] found that Au n on TiO 2 have a good catalytic activity in CO low-temperature oxidation reaction. Further deep explorations of Au n uncovered that Au n not only exhibited a variety of physical and chemical features [2][3][4], but also had broad applications in many fields, such as catalysis, biological engineering, nanotechnology, and so on [5][6][7][8][9][10]. More importantly, the study on the Au n is still the research focus even now.…”
Section: Introductionmentioning
confidence: 99%